(untitled) (Journal of the College of Education for Women, 2019)
In order to get an idea about things closely, we should look at the role of social disciplinein the building of society from civilization cultural viewpoint. The real weigh of the societalopinion is not measured by the number of its population or its area but the real value lies in itscivilization cultural accumulative experience inherited by the generations, which determine itsdistinguished character. That is based upon the social construction in which the methods ofsocialization and political, economic, cultural and religious stability and enhance the nationaland ethical character of self-realization.In this research, we try to give an analysis for the obstacles in political economic andreligious social construction. We think that of social construction is a process not by oneindividual but all the society.